Airway Y-stent Insertion in Tracheobronchomalacia: A New Experience - YC, Kuan; SH, How; TH, Ng; CK, Liam; A, Mohd Ashri; AR, Mohammed Fauzi (IIUM Medical Journal Malaysia, 2012)
This case report describes a rigid bronchoscopy-assisted placement of a silicone airway Y-stent in a patient who developed tracheobronchomalacia following repeated dilatations for post-tuberculous airway stenosis. This is the first report of an airway Y-stent insertion in Malaysia.